ADVANTAGES OF APPLYING A HYBRID SYSTEM IN VEHICLES - Mukimova Davlatkhan Karimovna (TADQIQOTLAR, 2025)
Abstract. This article describes the advantages of using a hybrid system in cars. The use of renewable sources is also covered.